A study of interprofessional education and working in healthcare: A longitudinal study of attitudes towards interprofessional education and working among healthcare undergraduate students - MC ADAM, MARGARET (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2018)
Background The genesis of this study evolved in response to the global recognition that effective interprofessional working (IPW) between healthcare professionals is vital for safer, quality patient/client care and primary healthcare delivery within the healthcare service, and to the subsequent call for development and implementation of interprofessional education (IPE) in healthcare courses in Higher Education Institutions around the world. Traditionally, healthcare students complete their professional courses in a uni-professional context, which no longer presents a viable solution to enable healthcare graduates to work interprofessionally. However, worldwide literature reports that successful outcomes for IPE and effective IPW are associated with attitudes relating to value attributed to IPW, strength of professional identity, professional stereotyping, and readiness for interprofessional learning. This study aimed to investigate these important influences to inform the development of IPE interventions. Methods A longitudinal cohort survey which took place in a Faculty of Health Sciences in one of the largest Higher Education Institutions (HEI) in the Republic of Ireland. This institution provides courses for all frontline professions in healthcare. The sample included first year undergraduate dietetic, medical, nursing, occupational therapy, pharmacy and physiotherapy students. Data was collected on course commencement and 12 months later. A non-healthcare group served as a comparator. Results The value placed on IPW and readiness for interprofessional learning was high at both timepoints. Students also presented with strong professional identity that was sustained into the following year. A highly statistically significant increase was observed at T2 for the healthcare group (p < 0.001) that was not observed in the comparator group on value attributed to IPW. Differences between healthcare groups on value and importance of IPW, strength of professional identity and readiness for interprofessional learning emerged at both timepoints. Students entered courses with pre-conceived stereotyped views with moderation across timepoints in some groups. Positive correlations were found between heterostereotypes/autostereotypes and readiness for IPE at baseline. Gender differences emerged with females indicating sustained higher readiness for IPE and higher value on IPW. Gender, strength of professional identity, and value attributed to interprofessional team working, were statistically significant to predict readiness for interprofessional learning (p < 0.001). Conclusion These study results have implications for the timing, structure, design and theoretical underpinnings of IPE in undergraduate healthcare education in both clinical and academic settings, and have made a unique contribution to the body of global evidence involving an Irish population of undergraduate healthcare students. IPE holds a key to improving IPW and effectively executed, has potential to positively impact on the safety and quality of patient/client care within our Irish healthcare service.
APPROVED
Keywords: Health education; Healthcare students